INNOVATIVE APPROACHES FOR THE DEVELOPMENT OF CREATIVITY OF CHILDREN IN EDUCATIONAL SCHOOLS OF EDUCATION - Baranovska, Iryna; Chernyatinska, Anastasia; Pokhyla, Svitlana (Educological discourse, 2019)
Text of the abstract. The article reveals the problems of development of children's creative talent in out-of-school educational institutions. It has been determined that gifted children (children with special educational problems) are the most vulnerable in society in the modern educational space. They require special attention from teachers, parents, psychologists and doctors in the process of education, training, adaptation, socialization and personality realization in a fast changing world. The uniqueness of the concept of "creative talent" of the child is proved. The work of scientists is analyzed, components and indices of child giftedness are studied. Indicators of giftedness are abilities (intellectual, artistic, musical, choreographic, artistic, technical, sports) to a certain type of activity. Creative abilities form the basis of the development of creative talent of the child. Out-of-school educational institutions in Ukraine have long-standing traditions of teaching and upbringing students according to their interests, preferences, and individual abilities. The principles of their activities allow taking into account the individual characteristics of each child. The multifaceted system of interrelated pedagogical techniques and technologies enables a wide range of content, forms and means of teaching students, provides an alternative to meeting the spiritual needs of the child, her interests, cognitive and intellectual opportunities based on the differentiation and individualization of the educational process. The reseаrch is based on the example of the work of the Vinnytsia regional station of young naturalists. Researchers need further attention to identify early gifted preschoolers, ensuring the continuity of the development of giftedness of children of preschool and primary school age.